2010
DOI: 10.1182/blood-2009-12-255125
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ and tumor necrosis factor-α induce an immunoinhibitory molecule, B7-H1, via nuclear factor-κB activation in blasts in myelodysplastic syndromes

Abstract: During disease progression in myelodysplastic syndromes (MDS), clonal blasts gain a more aggressive nature, whereas nonclonal immune cells become less efficient via an unknown mechanism. Using MDS cell lines and patient samples, we showed that the expression of an immunoinhibitory molecule, B7-H1 (CD274), was induced by interferon-␥ (IFN␥) and tumor necrosis factor-␣ (TNF␣) on MDS blasts. This induction was associated with the activation of nuclear factor-B (NF-B) and nearly completely blocked by an NF-B inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
167
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(176 citation statements)
references
References 48 publications
7
167
0
2
Order By: Relevance
“…36,37 Extrinsic PD-L1 expression is thought to be induced by cytokines, especially IFNg, in the tumor environment via various downstream pathways. [17][18][19] Because PD-L1 expression in PeSCC cells can be either intrinsic or extrinsic, studies investigating the precise pathways involved are currently underway in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36,37 Extrinsic PD-L1 expression is thought to be induced by cytokines, especially IFNg, in the tumor environment via various downstream pathways. [17][18][19] Because PD-L1 expression in PeSCC cells can be either intrinsic or extrinsic, studies investigating the precise pathways involved are currently underway in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…16 Cytokines, especially interferon-gamma (IFNg), that are expressed by activated T cells can induce PD-L1 expression in the surrounding tumor cells via specific signaling pathways. [17][18][19] To better elucidate the correlation between PD-L1 expression and TILs in PeSCC, the mRNA expression levels of PD-L1, IFNg, and CD8 C were evaluated in 24 primary penile cancer specimens. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) showed a significant positive correlation between PD-L1 and IFNg or CD8 C ( Fig.…”
Section: Correlation Between Pd-l1 Expression and Ifng In Pesccmentioning
confidence: 99%
“…IL-12 can induce IFN-γ expression and secretion of T cells, NK cells and macrophages (Wysocka et al, 1995;Puddu et al, 1997), the promoter region of the human B7-H1 gene has an NF-κB motif ). IFN-γ upregulated B7-H1 expression in some cells via NF-κB signal pathway activation (Kondo et al, 2010;Huang et al, 2013). However, the molecular mechanisms of action regulating the gene expression of B7-H1 vary in both different cell types and distinct stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the possible mechanism of IL-12 exerts function in regulating B7-H1 expression; we investigated the expression of IFN-γ firstly, because IFN-γ has been well known to induce the expression of B7-H1 (Lee et al, 2005;Lee et al, 2006;Kondo et al, 2010). It was found that rIL-12 and Ad-IL-12-GFP treated groups produced a higher level of IFN-γ in the supernatants of monocyte-derived macrophages cocultured with SKOV3 system.…”
Section: Il-12 Increased the Level Of Ifn-γ And Decreased The Level Omentioning
confidence: 99%
“…With the disease progression, MDS blasts become less apoptotic with increased proliferative capacity, producing phenotypically immature clone of cells, whereas the T-cell compartment shows decreased proliferation and increased apoptosis [27][28][29][30][31][32]. Kondo et al in 2010 showed that the increased production of IFN-γ and TNFα enhances the proliferation of blasts through the expression of B7-H1 on MDS blasts and could be an early event in the disease progression [33]. Additionally, B7-H1 + blasts suppress proliferation of T cells and induce their apoptosis in in vitro co-cultures [33].…”
Section: Journal Of Molecular and Genetic Medicinementioning
confidence: 99%